2013
DOI: 10.1186/2050-2974-1-s1-o38
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of educational interventions in reducing negative attitudes and stigmatisation toward patients with anorexia nervosa

Abstract: Bannatyne and Stapleton: The effectiveness of educational interventions in reducing negative attitudes and stigmatisation toward patients with anorexia nervosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Analysing the EDSS at subscale level, some findings appear more consistent with those of previous research. The highest mean subscale value was Blame (M = 1.68 SD = 0.99), which is a recurrent finding in studies that have utilised the EDSS (Bannatyne & Abel, 2015;Bannatyne & Stapleton, 2017;Crisafulli et al, 2010). Though in the current study most respondents still disagreed with the Blame statements, the noticeably higher endorsement of these items compared with others indicates that blame is a pivotal aspect of AN stigma.…”
Section: An and Blamementioning
confidence: 78%
See 1 more Smart Citation
“…Analysing the EDSS at subscale level, some findings appear more consistent with those of previous research. The highest mean subscale value was Blame (M = 1.68 SD = 0.99), which is a recurrent finding in studies that have utilised the EDSS (Bannatyne & Abel, 2015;Bannatyne & Stapleton, 2017;Crisafulli et al, 2010). Though in the current study most respondents still disagreed with the Blame statements, the noticeably higher endorsement of these items compared with others indicates that blame is a pivotal aspect of AN stigma.…”
Section: An and Blamementioning
confidence: 78%
“…As the scale has previously demonstrated that it measures the intended concept, its use increases the validity of results (Kazi & Khalid, 2012). Since its inception, the EDSS has been used in both full and adapted variants and has demonstrated Cronbach's alpha values between 0.81 and 0.95 (Bannatyne & Abel, 2015;Bannatyne & Stapleton, 2015), showing excellent internal consistency -a measure of reliability (Field, 2013). Utilising the EDSS allows for direct comparisons between this research and other studies that have used the scale.…”
Section: Methodsmentioning
confidence: 95%